2016
DOI: 10.1111/jsap.12504
|View full text |Cite
|
Sign up to set email alerts
|

Serum C‐reactive protein and S100A12 concentrations in dogs with hepatic disease

Abstract: Increased serum C-reactive protein and S100A12 concentrations were observed in a subpopulation of dogs with various types of hepatic diseases, suggesting acute-phase inflammation and activation of phagocytic cells, respectively. Dogs with higher hepatic necroinflammatory activity scores tended to have higher serum C-reactive protein concentrations. Further studies are needed to confirm this finding in a larger group of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 39 publications
1
20
4
3
Order By: Relevance
“…A key limitation of our findings was the substantial overlap in concentrations of IL‐6, CCL2, and CRP between dogs grouped by necroinflammatory or fibrosis scores. Overlap between affected and unaffected animals also has been reported for these and other biomarkers in dogs with liver disease, including IL‐6, CRP, interleukin 8, tumor necrosis factor alpha, hyaluronic acid, and PIIINP . The overlap observed in our study may have been due, in part, to heterogeneity in the types of liver diseases that we included.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…A key limitation of our findings was the substantial overlap in concentrations of IL‐6, CCL2, and CRP between dogs grouped by necroinflammatory or fibrosis scores. Overlap between affected and unaffected animals also has been reported for these and other biomarkers in dogs with liver disease, including IL‐6, CRP, interleukin 8, tumor necrosis factor alpha, hyaluronic acid, and PIIINP . The overlap observed in our study may have been due, in part, to heterogeneity in the types of liver diseases that we included.…”
Section: Discussionsupporting
confidence: 66%
“…Our study, as well as previously reported studies of liver biomarkers in dogs have enrolled relatively few dogs with cirrhosis. This is an important limitation because many biomarker studies in humans focus on distinguishing cirrhotic from non‐cirrhotic patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is a very sensitive and specific marker of localized inflammatory processes, such as gastrointestinal inflammation,128 and can be increased in serum with various inflammatory disorders 47, 116, 118, 129, 130. In contrast to calprotectin, corticosteroid treatment does not affect serum S100A12 concentrations 131…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%